Electrolyte, battery monomer, battery and electric device
By adding fluorophosphate, borate, and sulfate alinhellytic compounds to the electrolytes of lithium batteries to form a stable SEI film, solve the problem of frequent side reactions of lithium batteries under high current density conditions, significantly improved the battery of the battery Life life.
Patent Information
- Application Number
- CN202411540228.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-12
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-28
AI Technical Summary
Existing lithium batteries have shortcomings in their service life, especially under fast charging conditions with high current density, which are prone to side reactions, resulting in shortening of battery life.
Add fluorphosphate and borate as the first additive to the electrolyte, as well as a sulfate allexic compound as the second additive to form a stable SEI film, block the contact between the electrolyte and the active material, and reduce the side reaction.
By reducing the side reaction of the side and the side of the positive chip and the electrolyte, the service life of the lithium battery is significantly improved, and the gas production performance of the battery is improved.
Smart Images

Figure CN119381562A_ABST
Abstract
Description
[0001] Cross-references
[0002] This application refers to Chinese Patent Application No. 202410282198.0 filed on March 12, 2024, entitled “An electrolyte, a battery cell, a battery and an electrical device”, which is incorporated into this application in its entirety by reference. Technical Field
[0003] The present application relates to the field of battery technology, and in particular to an electrolyte, a battery cell, a battery and an electrical device. Background Art
[0004] Secondary batteries such as lithium batteries are increasingly widely used due to their clean and renewable characteristics, and have a large specific energy density and a long cycle life. They have been widely used in many fields such as consumer electronics, electric vehicles and energy storage. With the expansion of the application scope of secondary batteries, the service life of batteries has received more and more attention. Summary of the invention
[0005] In view of the above problems, the present application provides an electrolyte, a battery cell, a battery and an electrical device, which can increase the service life of a secondary battery.
[0006] In a first aspect, the present application provides an electrolyte, the components of the electrolyte including a first additive and a second additive, the first additive including at least one of fluorophosphate and borate, and the second additive including a vinyl sulfate compound.
[0007] In the technical solution of the embodiment of the present application, a first additive and a second additive are added to the electrolyte. Since the first additive fluorophosphate and / or borate has a lower LUMO energy level, it is easier to obtain electrons and be reduced when added to the electrolyte, which is conducive to forming a stable SEI film on the surface of the negative electrode active material, blocking the contact between the electrolyte and the negative electrode active material, thereby reducing the occurrence of electrolyte reduction, thereby inhibiting further side reactions on the negative electrode sheet side. Fluorophosphate and / or borate can also combine with metal ions on the surface of the positive electrode active material to form ionic bonds, reduce the phenomenon of lithium removal on the surface of the positive electrode active material, thereby effectively reducing the occurrence of structural destruction of the positive electrode active material and reducing the side reactions of the electrolyte on the positive electrode sheet side. By reducing the side reactions of the negative electrode sheet side and the positive electrode sheet side with the electrolyte, the life of the battery is improved.
[0008] The second additive, vinyl sulfate, is beneficial to promote the formation of electrolyte film on the surface of negative electrode active material, especially at high current density, protecting negative electrode active material from further corrosion, which is beneficial to the life of the battery and can improve the gas production of the battery. The first additive and the second additive work together to promote the formation of a more uniform, dense and stable negative electrode SEI film, thereby improving the life of the battery.
[0009] In some embodiments, the mass content b1 of the first additive in the electrolyte is 0.15%-2.5%; and / or
[0010] The mass content c1 of the second additive in the electrolyte is 0.05%-3.5%.
[0011] In the above implementation process, the greater the mass content of the first additive in the electrolyte, the more conducive it is to the formation of a stable SEI film on the surface of the negative electrode active material and the metal ions on the surface of the positive electrode active material to form ionic bonds, thereby reducing the side reactions between the negative electrode sheet and the positive electrode sheet and the electrolyte, which is beneficial to the life of the battery. The smaller the mass content of the first additive in the electrolyte, the more conducive it is to reducing the viscosity of the electrolyte. By controlling the mass content b1 of the first additive to 0.15%-2.5%, the dynamic performance and life of the battery can be taken into account.
[0012] In the above implementation process, the greater the mass content of the second additive in the electrolyte, the more conducive it is to the film formation on the surface of the negative electrode active material in the battery, which is beneficial to the life of the battery and improves the gas production of the battery. The smaller the mass content of the second additive in the electrolyte, the more conducive it is to reducing the battery impedance. By controlling the mass content c1 of the second additive in the electrolyte to 0.05%-3.5%, the performance of long battery life and low impedance can be taken into account.
[0013] In some embodiments, the mass content b1 of the first additive in the electrolyte is 0.5%-1.5%; and / or
[0014] The mass content c1 of the second additive in the electrolyte is 0.1%-2.5%.
[0015] In the above implementation process, controlling the mass content b1 of the first additive to 0.5%-1.5% can better balance the dynamic performance and life of the battery. Controlling the mass content c1 of the second additive in the electrolyte to 0.1%-2.5% can better balance the performance of the battery such as long life and low impedance.
[0016] In some embodiments, the fluorophosphate includes at least one of monofluorophosphate and difluorophosphate; and / or the borate includes at least one of tetrafluoroborate, bisoxalatoborate, and fluorine-containing oxalatoborate; and / or the fluorophosphate and borate each independently include at least one of lithium salt, sodium salt, and potassium salt; and / or
[0017] Vinyl sulfate compounds include At least one of .
[0018] In the above embodiments, fluorophosphate and / or borate have a lower LUMO energy level. When added to the electrolyte, it is easier for them to obtain electrons and be reduced, forming a stable SEI film on the surface of the negative electrode active material, which can block the contact between the electrolyte and the surface of the negative electrode active material, thereby inhibiting further side reactions on the negative electrode sheet side. At the same time, fluorophosphate and / or borate can combine with metal ions on the surface of the positive electrode active material to form ionic bonds, reduce the phenomenon of lithium removal on the surface of the positive electrode active material, thereby effectively reducing the occurrence of structural destruction of the positive electrode active material and reducing the side reactions of the electrolyte on the positive electrode sheet side. By reducing the side reactions between the negative electrode sheet side and the positive electrode sheet side and the electrolyte, it is beneficial to the life of the battery.
[0019] In the above embodiments, the vinyl sulfate compounds are rich in cyclic sulfate groups, and can form a lithium sulfate-rich SEI film on the negative electrode active material layer, and have good thermal stability, thereby improving the battery life.
[0020] In some embodiments, the first additive includes at least one of lithium difluorophosphate and lithium bis(oxalatoborate); and / or
[0021] The second additive includes At least one of .
[0022] In some embodiments, the mass ratio of lithium difluorophosphate to lithium difluorooxalatoborate is 1:(0.05-15).
[0023] In the above embodiment, the mass ratio of lithium difluorophosphate and lithium difluorooxalatoborate is within an appropriate range, and their combined effect can promote the formation of a more uniform, dense and stable SEI film, which can effectively reduce the decomposition of the electrolyte on the negative electrode side, thereby improving the cycle life and long-term stability of the battery.
[0024] In some embodiments, the electrolyte includes the second additive including a sulfonate compound, the mass content of the sulfonate compound in the electrolyte is 0.05%-0.5%, and / or the sulfonate compound includes In the above embodiment, the sulfonate compound is rich in cyclic sulfate groups. Adding the sulfonate compound to the electrolyte can further form a lithium sulfate-rich SEI film on the negative electrode active material layer, which has good thermal stability, thereby improving the battery life.
[0025] In some embodiments, the electrolyte comprises Said The mass ratio is 1: (0.25-7); or, the electrolyte comprises Said The mass ratio is 1:((0.25-7).
[0026] In the above embodiments, the mass ratio of sulfonate compounds and vinyl sulfate compounds is within an appropriate range, and their combined effect can promote the formation of a more uniform, dense and stable SEI film, which can effectively reduce the decomposition of the electrolyte on the negative electrode side, thereby improving the cycle life and long-term stability of the battery.
[0027] In some embodiments, the solvent includes at least one of a carboxylate compound and a carbonate compound, and the carboxylate compound includes: 1 -COO-R 2 , where R 1 Including H or C1-C5 alkyl, R 2 Including C1-C5 alkyl,
[0028] Carbonate compounds include At least one of the following, where R 3 Including C2-C3 alkylene, R 4 Includes C1-C2 alkyl, R5 includes C1-C2 alkyl.
[0029] In some embodiments, the carboxylate compound includes at least one of ethyl acetate, methyl acetate, methyl formate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, propyl butyrate, butyl butyrate, isopropyl acetate and isoamyl acetate; and / or the carbonate compound includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate and dimethyl carbonate.
[0030] In the above embodiment, the carboxylate compound has a relatively low viscosity (<0.6 mPa·s), which can reduce the migration resistance of lithium ions in the electrolyte, facilitate the diffusion of lithium ions in the electrolyte, and improve the fast charging and power performance of the battery.
[0031] In the above embodiments, ethylene carbonate and propylene carbonate have a relatively high dielectric constant, which can dissolve electrolytes well and improve the conductivity of the electrolyte, so that the battery can handle a larger current in a short time, and improve the fast charging performance of the battery. Ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate have relatively low viscosities, which can improve the flow properties of the electrolyte, help increase the diffusion rate of lithium ions in the electrolyte, help balance the relationship between the viscosity of the electrolyte and the solubility of the electrolyte, and optimize the fast charging performance of the battery.
[0032] In some embodiments, the mass content of the carboxylate compound in the electrolyte is 10%-70%; or
[0033] The mass content of the carbonate compound in the electrolyte is 30%-100%.
[0034] In the above embodiment, the greater the mass content of the carboxylate compound in the electrolyte, the more conducive it is to reducing the viscosity of the electrolyte, which is conducive to the diffusion of lithium ions in the electrolyte, and improving the fast charging and power performance of the battery. The lower the mass content of the carboxylate compound in the electrolyte, the greater the viscosity of the electrolyte, but the gas production and life problems will be alleviated. Controlling the mass content of the carboxylate compound in the solvent to 10%-70% can take into account both the dynamic performance and life of the battery.
[0035] In the above embodiments, the greater the mass content of ethylene carbonate and propylene carbonate in the electrolyte, the more conducive it is to improving the conductivity of the electrolyte and improving the fast charging performance of the battery. However, excessive mass content of ethylene carbonate and propylene carbonate will make the viscosity of the electrolyte too high, which is not conducive to the diffusion of the electrolyte in the electrolyte. Ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate have low viscosity and strong fluidity. The greater their mass content in the electrolyte, the more conducive it is to the migration of the electrolyte, thereby improving the fast charging performance of the battery.
[0036] In some embodiments, the electrolyte includes an electrolyte, the electrolyte includes a lithium salt, and the lithium salt includes LiPF 6 and at least one of LiFSI.
[0037] In some embodiments, the electrolyte includes LiPF 6 and LiFSI, LiFSI and LiPF 6 The molar ratio is 0.1-5, and / or the LiPF 6 The mass ratio of LiFSI is 0.1-10.
[0038] In the above implementation process, the higher the content of LiFSI, the more favorable it is for Li +The migration of LiFSI can improve the fast charging performance of the battery. The lower the content of LiFSI, the less corrosion of the negative electrode current collector can be reduced, which is beneficial to the safety performance of the battery. 6 The usage can take into account both the fast charging performance and safety of the battery.
[0039] In some embodiments, the viscosity of the electrolyte is ≤5 mPa·s.
[0040] In the above implementation process, the reduction of electrolyte viscosity is conducive to the diffusion of lithium ions in the electrolyte, thereby effectively improving the fast charging and power performance of the battery. By controlling the viscosity of the electrolyte to ≤5mPa·s, the battery with the electrolyte has better fast charging and power performance.
[0041] In a second aspect, the present application provides a battery cell, the battery cell comprising the electrolyte provided in the first aspect.
[0042] In the technical solution of the embodiment of the present application, by adding a first additive and a second additive to the electrolyte, the first additive includes fluorophosphate and / or borate, and the second additive includes a vinyl sulfate compound. The first additive and the second additive are conducive to the electrolyte forming a stable SEI film on the surface of the negative electrode active material, which can block the contact between the electrolyte and the negative electrode sheet, thereby inhibiting further side reactions on the negative electrode sheet side. At the same time, the first additive can combine with the metal ions on the surface of the positive electrode active material to form an ionic bond, reduce the phenomenon of lithium over-desorption on the surface of the positive electrode sheet, thereby effectively reducing the occurrence of structural destruction of the positive electrode active material and reducing the side reactions of the electrolyte on the positive electrode sheet side. By reducing the side reactions between the negative electrode sheet side and the positive electrode sheet side and the electrolyte, the battery life is beneficial.
[0043] In some embodiments, the mass content b2 of the first additive in the electrolyte is 0%-1%; and / or
[0044] The mass content c2 of the second additive in the electrolyte is 0%-2%.
[0045] In some embodiments, the battery cell further comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises lithium nickel cobalt manganese oxide, and the Dv50 of the lithium nickel cobalt manganese oxide is 2 μm-15 μm.
[0046] In the above embodiment, in a battery whose positive electrode active material of the positive electrode sheet is lithium nickel cobalt manganese oxide (for example, a ternary system), the first additive can combine with the metal ions on the surface of the positive electrode sheet to form ionic bonds, reduce the phenomenon of lithium over-desorption on the surface of the positive electrode sheet, thereby effectively reducing the occurrence of structural destruction of the positive electrode active material, reducing the side reactions of the electrolyte on the positive electrode sheet side and the gas production caused by the side reactions. When the second additive is added to the electrolyte, a CEI film can be further formed on the surface of the positive electrode active material, thereby improving the structural stability of the positive electrode sheet side, reducing the risk of gas production, and increasing the life of the battery.
[0047] The smaller the particle size of the positive electrode active material, the greater the impact on the interface side reaction. In the above embodiment, the particle size of the lithium nickel cobalt manganese oxide positive electrode active material is within an appropriate range, the positive electrode active material has many reaction sites, the lithium ion deintercalation speed is improved, and it can match the transmission speed of lithium ions in the electrolyte, which helps to reduce the lithium ion transmission impedance and the temperature rise of the battery under the fast charging system. At the same time, it can reduce the interface side reaction caused by the small particle size of the positive electrode active material, reduce the gas production caused by the side reaction and the impact of the side reaction on the battery life, and better balance the fast charging performance and service life of the battery.
[0048] In some embodiments, the battery cell further includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material includes a lithium-containing phosphate, and the Dv50 of the lithium-containing phosphate is 0.3 μm-2 μm.
[0049] In batteries whose positive electrode active material is a lithium phosphate material (including lithium iron manganese phosphate materials), the additive can form a stable SEI film on the negative electrode, blocking the contact between the solvent, especially the low-viscosity solvent, and the negative electrode, reducing the reduction gas production side reaction of the solvent on the negative electrode side, and improving the battery life.
[0050] In the above embodiments, the particle size of the lithium phosphate positive electrode active material (including lithium iron manganese phosphate materials) is controlled within an appropriate range, the positive electrode active material has more reaction sites, the lithium ion deintercalation speed is improved, and it can match the transmission speed of lithium ions in the electrolyte, which helps to reduce the lithium ion transmission impedance and the temperature rise of the battery under the fast charging system. At the same time, it can reduce the interface side reactions caused by the small particle size of the positive electrode active material and the excessive water absorption, thereby reducing the hydrolysis of the electrolyte caused by the side reactions and the impact of the side reactions on the battery life, while improving the battery fast charging performance while taking into account the battery cycle performance and service life.
[0051] In some embodiments, the positive electrode active material includes lithium nickel cobalt manganese oxide, the molar content of nickel element is less than 80% based on the total molar number of transition metals in the positive electrode active material, the Dv50 of the positive electrode active material is 2μm-5μm, and the positive electrode active material includes unagglomerated primary particles.
[0052] The molar content of nickel element is less than 80%, which is beneficial to reduce the probability of nickel dissolution of positive electrode active materials under high voltage (charging cut-off voltage ≥ 4.3V) and improve the withstand voltage of positive electrode active materials. The combination of low nickel components and unagglomerated primary particles can further reduce the degree of side reactions between positive electrode active materials and solvents, reduce the probability of cracking of positive electrode active materials during high voltage charging and discharging, and improve the cycle performance of battery cells. At the same time, primary particles have a higher specific surface area and a smaller particle size, which is beneficial to increase the rate of lithium ion insertion / extraction process and improve the fast charging performance of the battery. The Dv50 of the primary particles is 2μm-5μm. While improving the fast charging performance of the battery, it also takes into account the stability of the structure of the positive electrode active material, which is beneficial for the battery to maintain stable cycle performance.
[0053] In some embodiments, the positive electrode active material includes lithium nickel cobalt manganese oxide, based on the total molar number of transition metals in the positive electrode active material, the molar content of nickel element is greater than or equal to 80%, the Dv50 of the positive electrode active material is 6μm-15μm, and the positive electrode active material includes secondary particles formed by agglomeration of primary particles, and the average particle size of the primary particles in the secondary particles is 0.1μm-1.5μm.
[0054] Molding high-nickel materials into large-sized secondary particles is beneficial to simultaneously improve the specific capacity of the positive electrode active material and the grading of the positive electrode sheet, and improve the energy density of the battery. At the same time, the secondary particles are composed of primary particles with small particle sizes, which can shorten the transmission distance of lithium ions, increase the number of embedded end faces, reduce the DC impedance of the battery cells, and improve the power performance of the battery cells. The Dv50 of the secondary particles is 6μm-15μm, which can improve the energy density of the battery while taking into account the transmission distance of lithium ions and improving the fast charging performance of the battery. Controlling the average particle size of the primary particles in the secondary particles can shorten the transmission distance of lithium ions, increase the number of embedded end faces, reduce the DC impedance of the battery cells, and improve the power performance of the battery cells.
[0055] In some embodiments, the positive electrode active material includes unagglomerated primary particles and / or primary particles agglomerated to form secondary particles of lithium-containing phosphate, and the average particle size of the primary particles of the positive electrode active material is 50nm-300nm. The lithium-containing phosphate with an average particle size of primary particles within the above range has both a shorter ion transmission path and a low lithium ion transmission impedance, which can match the liquid phase transmission rate of lithium ions in the electrolyte and take into account the cycle life of the battery cell.
[0056] In some embodiments, the battery cell further comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based material and lithium metal.
[0057] In some embodiments, the negative electrode active material includes artificial graphite; and / or
[0058] The negative electrode active material includes secondary particles, and the Dv50 of the secondary particles is 5 μm-18 μm; and / or
[0059] Air oxidation temperature T of negative electrode active material 0 It is 630℃-730℃.
[0060] In the above embodiment, the artificial graphite has fewer defects, which can reduce the side reaction with the electrolyte, reduce gas production, and improve the gas production defects of the battery.
[0061] In the above embodiment, the secondary particles help to increase the reactive sites of the negative electrode active material, can provide a suitable embedding end surface for lithium ions, increase the de-embedding speed of lithium ions and improve the fast charging performance. The Dv50 of the negative electrode active material is 5μm to 18μm, which improves the fast charging performance of the battery while controlling the side reactions of the negative electrode active material and the electrolyte, and improves the cycle life of the battery.
[0062] In the above embodiment, the air oxidation temperature of the negative electrode active material is T 0 The temperature is 630℃-730℃, the negative electrode active material has good surface quality, the lithium ion embedding end face is suitable, and it can match the lithium ion transmission rate of the electrolyte, improving the fast charging performance of the battery. At the same time, the negative electrode active material has more lithium embedding positions, which is beneficial to improving the energy density of the battery. The negative electrode active material works synergistically with the first and second additives to form a dense SEI film on the surface of the negative electrode active material, which improves the fast charging performance of the battery while taking into account the cycle performance and service life of the battery.
[0063] In some embodiments, the negative electrode active material includes a silicon-based material, and the mass proportion of the silicon-based material in the negative electrode active material layer does not exceed 25%.
[0064] In a third aspect, the present application provides a battery, comprising the battery cell provided in the second aspect.
[0065] In some embodiments, the charging time t for charging the battery from 0% SOC to 80% SOC satisfies: t≤18.5 min.
[0066] In a fourth aspect, the present application provides an electrical device, which includes the battery provided in the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0068] Figure 1 A schematic diagram of the structure of a vehicle provided in some embodiments of the present application;
[0069] Figure 2 A schematic diagram of the exploded structure of a secondary battery provided in some embodiments of the present application;
[0070] Figure 3 A schematic diagram of the structure of a battery cell provided in some embodiments of the present application;
[0071] Figure 4 An exploded view of a battery cell provided for some embodiments of the present application.
[0072] The reference numerals in the specific implementation manner are as follows:
[0073] 1000-vehicle; 100-secondary battery; 200-motor; 300-controller; 10-housing; 11-accommodating space; 12-first part; 13-second part; 20-battery cell; 21-housing; 211-opening; 22-end cover assembly; 221-end cover; 222-electrode terminal; 23-electrode assembly; 24-current collecting member; 25-insulating protection member. DETAILED DESCRIPTION
[0074] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0075] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0076] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0077] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0078] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0079] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0080] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0081] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0082] The market's requirements for the cycle performance of power batteries such as sodium-ion batteries and lithium-ion batteries are gradually increasing, and at the same time, expectations for the fast charging capabilities of batteries are also increasing. Fast charging conditions with high current density can shorten the charging time, but secondary batteries are prone to local overheating under fast charging conditions with high current density, which can easily make the SEI film unstable and easily damaged, aggravate the side reactions of the electrolyte and active materials and the decomposition of the electrolyte, and reduce the battery life.
[0083] Therefore, the present application proposes an electrolyte, the components of the electrolyte include a first additive and a second additive, the first additive includes at least one of fluorophosphate and borate, and the second additive includes a vinyl sulfate compound.
[0084] In such an electrolyte, by adding the first additive and the second additive to the electrolyte, since the first additive fluorophosphate and / or borate has a lower LUMO energy level, it is easier to obtain electrons and be reduced when added to the electrolyte, and a stable SEI film is formed on the surface of the negative electrode active material, which can block the contact between the electrolyte and the negative electrode active material, thereby reducing the occurrence of electrolyte reduction, thereby inhibiting further side reactions on the negative electrode sheet side. Fluorophosphate and / or borate can also combine with metal ions on the surface of the positive electrode active material to form ionic bonds, reduce the phenomenon of lithium removal on the surface of the positive electrode active material, thereby effectively reducing the occurrence of structural destruction of the positive electrode active material and reducing the side reactions of the electrolyte on the positive electrode sheet side. By reducing the side reactions of the negative electrode sheet side and the positive electrode sheet side with the electrolyte, the life of the battery is improved.
[0085] The second additive, vinyl sulfate, is beneficial to promote the formation of electrolyte film on the surface of negative electrode active material, especially at high current density, protecting negative electrode active material from further corrosion, which is beneficial to battery life and can improve battery gas production. The first additive and the second additive work together to promote the formation of a more uniform, dense and stable SEI film on the negative electrode, thereby extending the cycle life of the battery.
[0086] The electrolyte can be used to prepare battery cells, which can be but are not limited to being used in electrical devices such as vehicles, ships or aircraft. A power supply system comprising the battery cells, batteries, etc. disclosed in this application can be used to form the electrical device. An embodiment of the present application provides an electrical device, which uses the above battery as a power source. The electrical device can be but is not limited to a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, and the like. Among them, electric toys can include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, electric airplane toys, and the like, and spacecraft can include airplanes, rockets, space shuttles, spacecraft, and the like.
[0087] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device according to an embodiment of the present application.
[0088] Please refer to Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A secondary battery 100 is provided inside the vehicle 1000, and the secondary battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The secondary battery 100 may be used to power the vehicle 1000, for example, the secondary battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 300 and a motor 200, and the controller 300 is used to control the secondary battery 100 to power the motor 200, for example, for starting, navigating and driving the vehicle 1000.
[0089] In some embodiments of the present application, the secondary battery 100 can be used not only as an operating power source for the vehicle 1000 , but also as a driving power source for the vehicle 1000 , replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000 .
[0090] In the present application, the secondary battery 100 may refer to a single battery cell 20, or it may refer to a single physical module including multiple battery cells 20 to provide higher voltage and capacity, which may be in the form of a battery pack, a battery module, etc. The secondary battery 100 may include a case 10 for encapsulating multiple battery cells 20, and the case 10 may prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.
[0091] Figure 2 This is a schematic diagram of the exploded structure of a secondary battery 100 provided in some embodiments of the present application. Figure 2 The secondary battery 100 includes a housing 10 and a battery cell 20 , and the battery cell 20 is accommodated in the housing 10 .
[0092] The box body 10 is used to provide a storage space 11 for the battery cell 20. In some embodiments, the box body 10 may include a first portion 12 and a second portion 13, and the first portion 12 and the second portion 13 cover each other to define the storage space 11 for accommodating the battery cell 20. Of course, the connection between the first portion 12 and the second portion 13 can be sealed by a sealing member (not shown in the figure), and the sealing member can be a sealing ring, a sealant, etc.
[0093] The first part 12 and the second part 13 can be in various shapes, such as a cuboid, a cylinder, etc. The first part 12 can be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20, and the second part 13 can also be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20. The opening side of the second part 13 covers the opening side of the first part 12, thereby forming a box body 10 with a receiving space 11. Of course, if Figure 2 As shown, the first part 12 may be a hollow structure with one side open, and the second part 13 may be a plate-like structure. The second part 13 covers the open side of the first part 12 to form a box body 10 with an accommodating space 11.
[0094] In the secondary battery 100, there are multiple battery cells 20, and the multiple battery cells 20 can be connected in series, in parallel, or in mixed connection. Mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 can be directly connected in series, in parallel, or in mixed connection, and then the whole body formed by the multiple battery cells 20 is accommodated in the box 10; of course, multiple battery cells 20 can also be connected in series, in parallel, or in mixed connection to form a battery module, and then the multiple battery modules are connected in series, in parallel, or in mixed connection to form a whole body, and accommodated in the box 10. The battery cell 20 can be cylindrical, flat, rectangular, or other shapes. Figure 2 The example shows that the battery cell 20 is in a square shape.
[0095] In some embodiments, the secondary battery 100 may further include a busbar component (not shown), and the multiple battery cells 20 may be electrically connected via the busbar component to achieve series connection, parallel connection, or mixed connection of the multiple battery cells 20 .
[0096] Figure 3 This is a schematic diagram of the structure of a battery cell 20 provided in some embodiments of the present application. Figure 4 This is an exploded view of a battery cell 20 provided in some embodiments of the present application. Figure 3 and Figure 4 The battery cell 20 may include a housing 21 , an end cap assembly 22 and an electrode assembly 23 . The housing 21 has an opening 211 , the electrode assembly 23 is accommodated in the housing 21 , and the end cap assembly 22 is used to cover the opening 211 .
[0097] The shape of the housing 21 can be determined according to the specific shape of the electrode assembly 23. For example, if the electrode assembly 23 is a rectangular parallelepiped structure, the housing 21 can be a rectangular parallelepiped structure. Figure 3 and Figure 4 The case where the housing 21 and the electrode assembly 23 are square is exemplarily shown.
[0098] The shell 21 may also be made of a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc., and the embodiment of the present application does not impose any special restrictions on this.
[0099] The end cap assembly 22 includes an end cap 221 and an electrode terminal 222. The end cap assembly 22 is used to seal the opening 211 of the housing 21 to form a closed installation space (not shown), and the installation space is used to accommodate the electrode assembly 23. The installation space is also used to accommodate an electrolyte, such as an electrolyte. The end cap assembly 22 is a component for outputting the electrical energy of the electrode assembly 23. The electrode terminal 222 in the end cap assembly 22 is used to be electrically connected to the electrode assembly 23, that is, the electrode terminal 222 is electrically connected to the tab of the electrode assembly 23. For example, the electrode terminal 222 is connected to the tab through the current collecting member 24 to achieve electrical connection between the electrode terminal 222 and the tab.
[0100] It should be noted that the opening 211 of the shell 21 can be one or two. If the opening 211 of the shell 21 is one, the end cap assembly 22 can also be one, and two electrode terminals 222 can be provided in the end cap assembly 22, and the two electrode terminals 222 are respectively used to electrically connect to the positive pole ear and the negative pole ear of the electrode assembly 23. If the opening 211 of the shell 21 is two, for example, the two openings 211 are provided on opposite sides of the shell 21, the end cap assembly 22 can also be two, and the two end cap assemblies 22 are respectively covered at the two openings 211 of the shell 21. In this case, the electrode terminal 222 in one end cap assembly 22 can be a positive electrode terminal 222, which is used to electrically connect to the positive pole ear of the electrode assembly 23; the electrode terminal 222 in the other end cap assembly 22 can be a negative electrode terminal 222, which is used to electrically connect to the negative electrode sheet of the electrode assembly 23.
[0101] In some embodiments, Figure 4 As shown, the battery cell 20 may further include an insulating protective member 25 fixed to the periphery of the electrode assembly 23, and the insulating protective member 25 is used to insulate and isolate the electrode assembly 23 from the housing 21. Exemplarily, the insulating protective member 25 is a tape bonded to the periphery of the electrode assembly 23. In some embodiments, there are multiple electrode assemblies 23, and the insulating protective member 25 is arranged around the periphery of the multiple electrode assemblies 23, and the multiple electrode assemblies 23 are formed into an integral structure to keep the electrode assembly 23 structurally stable.
[0102] The electrode assembly 23 includes a positive electrode sheet, a negative electrode sheet and a separator. The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer is coated on the surface of the positive electrode current collector, the positive electrode current collector not coated with the positive electrode active material layer protrudes from the positive electrode current collector coated with the positive electrode active material layer, and the positive electrode current collector not coated with the positive electrode active material layer serves as a positive electrode tab. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is coated on the surface of the negative electrode current collector, the negative electrode current collector not coated with the negative electrode active material layer protrudes from the negative electrode current collector coated with the negative electrode active material layer, and the negative electrode current collector not coated with the negative electrode active material layer serves as a negative electrode tab. The material of the negative electrode current collector may be copper, and the negative electrode active material may be carbon or silicon, etc. In order to ensure that a large current passes without melting, the number of positive electrode tabs is multiple and stacked together, and the number of negative electrode tabs is multiple and stacked together. The material of the separator may be PP (polypropylene, polypropylene) or PE (polyethylene, polyethylene), etc. In addition, the electrode assembly 23 may be a laminated electrode assembly, but the embodiments of the present application are not limited thereto.
[0103] The type and content of the first additive and the second additive in the electrolyte can be tested by the following method: add 500 μl of deuterated reagent to the NMR tube in a glove box filled with nitrogen, take 100 μl of non-aqueous electrolyte sample and add it to the NMR tube, shake the NMR tube to dissolve the non-aqueous electrolyte in the deuterated reagent, and use the Oxford Instruments desktop NMR spectrometer X-Pulse for testing. Since non-aqueous electrolyte is very sensitive to moisture, the NMR test and sample preparation are carried out in a nitrogen atmosphere (H 2 O content is less than 0.1ppm, O 2 The content is less than 0.1ppm), and the test-related instruments also need to be pre-washed with pure water and dried in a vacuum environment at 60°C for more than 48 hours. Among them, the deuterated reagent is prepared according to the following steps: deuterated dimethyl sulfoxide (DMSO-d6), deuterated acetonitrile and trifluoromethylbenzene are dried with 4A molecular sieves at a temperature above 25°C for more than 3 days to ensure that the water content of all reagents is less than 3ppm. The moisture test instrument can use the 831KF coulometric moisture tester of Swiss Metrom Co., Ltd. After that, 10ml of dried DMSO-d6 and 300μl of dried internal standard trifluoromethylbenzene are mixed evenly in a glove box filled with nitrogen to obtain a first solution, 10ml of dried deuterated acetonitrile and 300μl of dried internal standard trifluoromethylbenzene are mixed evenly to obtain a second solution, and the first solution and the second solution are mixed evenly to obtain a deuterated reagent.
[0104] In some embodiments of the present application, the mass content b1 of the first additive in the electrolyte is 0.15%-2.5%.
[0105] In this article, "the mass content of the first additive in the electrolyte" means: the mass of the first additive divided by the mass of the entire electrolyte. The mass of the first additive can be measured by gas chromatography, gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), and inductively coupled plasma optical emission spectroscopy (ICP-OES).
[0106] The greater the mass content of the first additive in the electrolyte, the more conducive it is to the formation of the SEI film on the surface of the negative electrode active material and the ionic bond on the surface of the positive electrode active material, thereby reducing the side reactions between the negative electrode sheet and the positive electrode sheet and the electrolyte, which is beneficial to the life of the battery. The smaller the mass content of the first additive in the electrolyte, the more conducive it is to reducing the viscosity of the electrolyte. Controlling the mass content b1 of the first additive to 0.15%-2.5% can take into account both the kinetic performance and life of the battery.
[0107] Exemplarily, the mass content b1 of the first additive in the electrolyte can be 0.15%-2.0%, 0.15%-1.5%, 0.15%-1.0%, 0.15%-0.5%, 0.15%-0.2%. The mass content b1 of the first additive in the electrolyte can be 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4% or 2.5%, etc., and it can also be any value in the range of 0.15%-2.5%.
[0108] In some embodiments of the present application, the mass content b1 of the first additive in the electrolyte is 0.5%-1.5%. By controlling the mass content b1 of the first additive to be 0.5%-1.5%, the dynamic performance and life of the battery can be better balanced.
[0109] In some embodiments of the present application, the fluorophosphate includes at least one of monofluorophosphate and difluorophosphate; the borate includes at least one of tetrafluoroborate, bisoxalatoborate, and fluorine-containing oxalatoborate; the fluorophosphate and borate each independently include at least one of lithium salt, sodium salt, and potassium salt.
[0110] Exemplarily, the fluorophosphate can be selected from lithium monofluorophosphate, sodium monofluorophosphate, potassium monofluorophosphate, lithium difluorophosphate, sodium difluorophosphate, potassium difluorophosphate; the borate can be selected from at least one of lithium tetrafluoroborate, sodium tetrafluoroborate, potassium tetrafluoroborate, lithium bisoxalatoborate, sodium bisoxalatoborate, potassium bisoxalatoborate, fluorine-containing lithium oxalatoborate (e.g., lithium difluorooxalatoborate), fluorine-containing sodium oxalatoborate (e.g., sodium difluorooxalatoborate) or fluorine-containing potassium oxalatoborate (e.g., potassium difluorooxalatoborate), etc.
[0111] Further, the fluorophosphate can be selected from lithium difluorophosphate (LIPO 2 F 2 ), the borate may be selected from lithium difluorooxalatoborate (LIODFB).
[0112] In this application, lithium difluorooxalatoborate added to the electrolyte may be converted into lithium tetrafluoroborate. A simplified reaction formula can be expressed as: LiDFOB→LiBF 4 +CO 2 +H 2 O. This process can be very complex and may involve multiple intermediate steps. Therefore, in the case where the first additive contains lithium difluorooxalatoborate, there may be 100ppm-3000ppm of lithium tetrafluoroborate in the electrolyte.
[0113] Exemplarily, in the electrolyte of the present application, the mass content of lithium tetrafluoroborate is 100 ppm, 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm, 1200 ppm, 1400 ppm, 1600 ppm, 1800 ppm, 2000 ppm, 2200 ppm, 2400 ppm, 2600 ppm, 2800 ppm or 3000 ppm, and it can also be any value within the range of 100 ppm-3000 ppm.
[0114] In some embodiments of the present application, the first additive includes lithium tetrafluoroborate, and the amount of lithium tetrafluoroborate added to the electrolyte is b1. It can be understood that the amount of lithium tetrafluoroborate in the electrolyte, when added as an additive, and the amount converted from lithium difluorooxalatoborate, can be the same or different.
[0115] In some embodiments of the present application, the mass ratio of lithium difluorophosphate to lithium difluorooxalatoborate is 1:(0.05-15).
[0116] When the mass ratio of lithium difluorophosphate and lithium difluorooxalatoborate is within an appropriate range, their combined effect can promote the formation of a more uniform, dense and stable SEI film, which can effectively reduce the decomposition of the electrolyte on the negative electrode side, thereby improving the cycle life and long-term stability of the battery.
[0117] Exemplarily, the mass ratio of lithium difluorophosphate and lithium difluorooxalatoborate is 1:0.05, 1:0.1, 1:0.2, 1:0.5, 1:0.7, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, etc., and it can also be any value in the range of 1:(0.05-15).
[0118] In some embodiments of the present application, the mass content c1 of the second additive in the electrolyte is 0.05%-3.5%.
[0119] In this article, "the mass content of the second additive in the electrolyte" means: the mass of the second additive divided by the mass of the entire electrolyte. The mass of the second additive can be measured by gas chromatography, gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), nuclear magnetic resonance spectroscopy (NMR), and inductively coupled plasma optical emission spectroscopy (ICP-OES).
[0120] The greater the mass content of the second additive in the electrolyte, the more conducive it is to the film formation on the surface of the negative electrode active material in the battery, which is beneficial to the battery life and improves the gas production of the battery. The smaller the mass content of the second additive in the electrolyte, the more conducive it is to reducing the battery impedance. By controlling the mass content c1 of the second additive in the electrolyte to 0.05%-3%, it can cooperate with the first additive to take into account the low viscosity of the electrolyte and the long battery life and low impedance.
[0121] Furthermore, the mass content c1 of the second additive in the electrolyte is 0.1%-2.5%, which can better balance the performance of the battery such as long life and low impedance.
[0122] Exemplarily, the mass content c1 of the second additive in the electrolyte can be 0.05%-3%, 0.05%-2.5%, 0.05%-1.5%, 0.05%-1.0%, 0.05%-0.5%, 0.05%-0.1%. The mass content c1 of the second additive in the electrolyte can be 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or 3.5%, etc., and it can also be any value in the range of 0.05%-3.5%.
[0123] In some embodiments of the present application, the structural formula of the vinyl sulfate compound can be: Wherein, q is 1, 2 or 3, and optionally 1, R 17 and R 18Each is independently selected from a hydrogen atom, a halogen atom, a C2-C6 alkenyl group, a C1-C6 alkyl group, a C1-C6 haloalkyl group, a C1-C6 alkoxy group, a C1-C6 alkyloxyacyl group, a C1-C6 haloalkoxyacyl group, a C1-6 alkyl group and a 4-6 membered cyclic sulfate group; optionally R 17 and R 18 Each is independently selected from a hydrogen atom, a halogen atom, a C2-C4 alkenyl group, a C1-C4 alkyl group, a C1-C3 haloalkyl group, a C1-C3 alkoxy group, a C1-C3 haloalkoxy acyloxy group, a C1-C3 alkyl group and a 4-6 membered cyclic sulfate group; more optionally, R 17 and R 18 Each is independently selected from a hydrogen atom, a C1-C4 alkyl group, a C1-C3 alkyloxyacyl group; R 19 and R 20 are each independently selected from a hydrogen atom, a halogen atom, a C1-C6 alkyl group, a C1-C6 haloalkyl group, a C1-C6 alkoxy group, a C1-C6 haloalkoxy group and an aryl group; optionally, R 19 and R 20 Each is independently selected from a hydrogen atom, a halogen atom and a C1-C6 alkyl group.
[0124] Vinyl sulfate compounds are rich in cyclic sulfate groups and can form a lithium sulfate-rich SEI film on the negative electrode active material layer with good thermal stability, thereby improving battery life.
[0125] In some embodiments of the present application, the vinyl sulfate compound includes vinyl sulfate Vinyl Bisulphate and ethylene trisulfate At least one of .
[0126] Further, the vinyl sulfate compounds include vinyl disulfate and ethylene trisulfate At least one of .
[0127] In some technical solutions of the present application, the second additive includes a sulfonate compound, and the mass content of the sulfonate compound in the electrolyte is 0.05%-0.5%.
[0128] Exemplarily, the mass content of the sulfonate compound in the electrolyte is 0.05%-0.4%, 0.05%-0.3%, 0.05%-0.2%, 0.05%-0.1%. The mass content of the sulfonate compound in the electrolyte is 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%, etc., and it can also be any value in the range of 0.05%-0.5%.
[0129] For example, the sulfonate compound may be a sultone compound, and its structural formula may be: Wherein, p is 1, 2 or 3, and optionally 1; R 11 and R 12 are each independently selected from a hydrogen atom, a halogen atom, a C1-C6 alkyl group, a C1-C3 haloalkyl group, a C1-C3 alkoxy group and a C1-C3 haloalkoxy group; optionally, R 11 and R 12 are each independently selected from a hydrogen atom, a halogen atom, a C1-C3 alkyl group, a C1-C3 haloalkyl group; more optionally, R 11 is a hydrogen atom, and R 12 is a hydrogen atom, a C1-C3 alkyl group or a halogen atom; R 13 and R 14 are each independently selected from a hydrogen atom, a halogen atom, a C1-C6 alkyl group, a C1-C6 haloalkyl group, a C1-C6 alkoxy group and a C1-C3 haloalkoxy group; optionally, R 13 and R 14 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C3 alkyl group, a C1-C3 haloalkyl group, a C1-C3 alkoxy group and a C1-C3 haloalkoxy group, and more optionally R 13 and R 14 Each is independently a hydrogen atom or a C1-C3 alkyl group; R 15 and R 16 Each is independently selected from a hydrogen atom, a halogen atom, a C2-C6 alkenyl group, an ester group, a C1-C6 alkyl group, a C1-C6 haloalkyl group, a C1-C6 alkoxy group and a C1-C6 haloalkoxy group, and is optionally selected from a hydrogen atom, a C1-C3 alkyl group, a C1-C3 fluoroalkyl group and a C2-C3 alkenyl group; or R 15 and R 16 Together they form the carbonyl group.
[0130] In some technical solutions of the present application, the sulfonate compound includes 1,3-propane sultone and methylene methane disulfonate At least one of .
[0131] Sulfonate compounds are rich in cyclic sulfate groups and can form a lithium sulfate-rich SEI film on the negative electrode active material layer, which has good thermal stability and improves battery life. They work synergistically with vinyl sulfate compounds to improve the stability of the SEI film.
[0132] In some technical solutions of the present application, the electrolyte includes Said The mass ratio is 1:(0.25-7).
[0133] In the above embodiments, the mass ratio of sulfonate compounds and vinyl disulfate compounds is within an appropriate range, and their combined effect can promote the formation of a more uniform, dense and stable SEI film, which can effectively reduce the decomposition of the electrolyte on the negative electrode side, thereby improving the cycle life and long-term stability of the battery.
[0134] For example, The mass ratio is 1:0.25, 1:0.5, 1:0.75, 1:1, 1:1.25, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5 or 1:7, etc., and it can also be any value in the range of 1:(0.25-7).
[0135] In some technical solutions of the present application, the electrolyte includes The mass ratio is 1:(0.25-7).
[0136] For example, The mass ratio of is 1:0.25, 1:0.5, 1:0.75, 1:1, 1:1.25, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5 or 1:7, etc., and it can also be any value in the range of 1:(0.25-7). In the above embodiment, the mass ratio of the sulfonate compound and the triethylene sulfate compound is within a suitable range, and the combined effect can promote the formation of a more uniform, dense and stable SEI film, which can effectively reduce the decomposition of the electrolyte on the negative electrode side, thereby improving the cycle life and long-term stability of the battery.
[0137] The charging time of power batteries such as sodium-ion batteries and lithium-ion batteries can reflect the fast charging performance of the battery. The shorter the time, the better the fast charging performance of the battery.
[0138] It should be noted that fast-charging batteries generally refer to batteries whose charging time t from 10% SOC to 80% SOC satisfies: t≤15min. That is, when the current density of a lithium-ion battery is greater than or equal to 2.8C, the charging time from 10% SOC to 80% SOC is less than or equal to 15min. This current density is the equivalent current density of a lithium-ion battery during the process of charging from 10% SOC to 80% SOC. In other words, in the process of charging from 10% SOC to 80% SOC, the current density I may gradually decrease from greater than 2.8C to less than 2.8C. In this process, lithium-ion batteries may undergo a transition from constant current charging to constant voltage charging, and thus, the current density is not constant. For example: start charging a lithium-ion battery at room temperature of 25°C, charging from 10% SOC to 80% SOC, and the charging time is 10 minutes (equivalent current I≥4C). The charging process is: initially at 5C from 10% SOC to 45% SOC, then at 4.6C from 45% SOC to 50% SOC, 4.3C from 50% SOC to 55% SOC, 3.9C from 55% SOC to 60% SOC, 3.6C from 60% SOC to 65% SOC, 3.3C from 65% SOC to 70% SOC, 3.1C from 70% SOC to 75% SOC, 2.9C from 75% SOC to 80% SOC, and the charging is completed. The charging time for lithium-ion batteries to charge from 0% SOC to 100% SOC at 1C is 60min. Therefore, when it is measured that the charging time of the lithium-ion battery from 10% SOC to 80% SOC is 10 minutes, the equivalent current density of the process can be calculated as: [(80% SOC-10% SOC) / (100% SOC-0% SOC)]×[(1C×60min) / 10min]=4.2C. Under the charging conditions of the lithium-ion battery, the time it takes to charge from 0% SOC to 100% SOC can also be directly recorded. For example, if the time is around 15 minutes (the error does not exceed 1 minute), it is generally considered to be a 4C fast-charging battery. For another example, if the time is around 12 minutes (the error does not exceed 1 minute), it is generally considered to be a 5C fast-charging battery. For another example, if the time is around 10 minutes (the error does not exceed 1 minute), it is generally considered to be a 6C fast-charging battery.
[0139] In some technical solutions of the present application, the electrolyte includes a solvent, and the solvent includes at least one of a carboxylate compound and a carbonate compound.
[0140] In some technical solutions of the present application, the carboxylic acid ester compound includes R 1 -COO-R 2 , where R 1 Including H or C1-C5 alkyl, R 2 Including C1~C5 alkyl groups.
[0141] Carboxylate compounds have a low viscosity (<0.6 mPa·s), which can reduce the migration resistance of lithium ions in the electrolyte, facilitate the diffusion of lithium ions in the electrolyte, and improve the fast charging and power performance of the battery.
[0142] Exemplarily, the carboxylate compound includes at least one of ethyl acetate (EA), methyl acetate (MA), methyl formate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, propyl butyrate, butyl butyrate, isopropyl acetate and isoamyl acetate.
[0143] In some embodiments of the present application, the carboxylate compound includes dimethyl carbonate and / or ethyl acetate.
[0144] In some embodiments of the present application, the mass content of the carboxylate compound in the electrolyte is 10%-70%.
[0145] Herein, "the mass content of the carboxylate compound in the solvent" refers to: the mass of the carboxylate compound in the electrolyte solvent divided by the mass of the entire electrolyte solvent.
[0146] The greater the mass content of carboxylic acid ester compounds in the electrolyte, the more conducive it is to reducing the viscosity of the electrolyte, which is conducive to the diffusion of lithium ions in the electrolyte, and improving the fast charging and power performance of the battery. The lower the mass content of carboxylic acid ester compounds in the electrolyte, the greater the viscosity of the electrolyte, but the gas production and life problems will be reduced. Controlling the mass content of carboxylic acid ester compounds in the solvent to 15%-70% can take into account both the dynamic performance and life of the battery.
[0147] Exemplarily, the mass content of the carboxylate compound in the solvent is 20%-60%, 25%-60%, 25%-50%, 25%-40%, 25%-30%. The mass content of the carboxylate compound in the solvent is 25%, 30%, 40%, 50%, 60% or 70%, etc., and it can also be any value within the range of 25%-70%.
[0148] In some technical solutions of the present application, the carbonate compound includes At least one of the following, where R 3 Including C2-C3 alkylene, R 4 Including C1-C2 alkyl, R 5 Includes C1-C2 alkyl.
[0149] Ethylene carbonate and propylene carbonate have a high dielectric constant, which can dissolve electrolytes well and improve the conductivity of the electrolyte, so that the battery can handle a larger current in a short time, and improve the battery's fast charging performance. Ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate have a low viscosity, which can improve the flow properties of the electrolyte, help increase the diffusion rate of lithium ions in the electrolyte, help balance the relationship between the viscosity of the electrolyte and the solubility of the electrolyte, and optimize the battery's fast charging performance.
[0150] Exemplarily, the carbonate compound includes at least one of ethylene carbonate (EC), propylene carbonate, ethyl methyl carbonate (EMC), diethyl carbonate, and dimethyl carbonate (DMC).
[0151] In some embodiments of the present application, the carbonate compound includes dimethyl carbonate.
[0152] In some embodiments of the present application, the mass content of the carbonate compound in the solvent is 30%-100%.
[0153] In this article, "the mass content of carbonate compounds in the solvent" refers to: the mass of carbonate compounds in the electrolyte solvent divided by the mass of the entire electrolyte solvent.
[0154] The greater the mass content of ethylene carbonate and propylene carbonate in the electrolyte, the more conducive it is to improving the conductivity of the electrolyte and improving the fast charging performance of the battery. However, excessive mass content of ethylene carbonate and propylene carbonate will make the viscosity of the electrolyte too high, which is not conducive to the diffusion of the electrolyte in the electrolyte. Ethyl methyl carbonate, diethyl carbonate, and dimethyl carbonate have low viscosity and strong fluidity. The greater their mass content in the electrolyte, the more conducive it is to the migration of the electrolyte, thereby improving the fast charging performance of the battery.
[0155] Exemplarily, the mass content of carbonate compounds in the solvent is 30%-90%, 30%-80%, 30%-70%, 30%-60%, 30%-50%, 30%-40%. The mass content of carbonate compounds in the solvent is 30%, 40%, 50%, 60%, 70%, 80%, 90% or 100%, etc., and it can also be any value within the range of 30%-100%.
[0156] In some embodiments of the present application, the solvent contains 20%-70% by mass of carboxylate compounds, and / or, the solvent contains 30%-80% by mass of carbonate compounds. Exemplarily, the solvent contains 70% by mass of carboxylate compounds and 30% by mass of carbonate compounds. Exemplarily, the solvent contains 30% by mass of ethylene carbonate and 70% by mass of ethyl methyl carbonate.
[0157] In some embodiments of the present application, the solvent contains 100% by weight of carbonate compounds.
[0158] The first additive and the second additive in the present application are applicable to a wide range of electrolyte systems, can promote the formation of a more uniform, dense and stable SEI film, effectively reduce the decomposition of the electrolyte on the negative electrode side, thereby improving the cycle life and long-term stability of the battery.
[0159] In some technical solutions of the present application, the electrolyte solvent may also include at least one of acid anhydride, N-methylpyrrolidone, N-methylformamide, N-methylacetamide, acetonitrile, cyclopentane, dimethyl sulfoxide, ethylene sulfite, propylene sulfite, methyl sulfide, diethyl sulfite, dimethyl sulfite, tetrahydrofuran, fluorine-containing cyclic organic esters, and sulfur-containing cyclic organic esters.
[0160] In some embodiments of the present application, the electrolyte includes an electrolyte, and the electrolyte can be selected from one or more of an organic electrolyte or an inorganic electrolyte. The electrolyte may contain one or more of nitrogen, sulfur, fluorine, boron, and phosphorus. The type of electrolyte is related to the type of secondary battery to which the electrolyte of the present application is applied. For example, when used in a lithium-ion battery, the electrolyte may be a lithium salt, and the lithium salt may be selected from one or more of an organic lithium salt or an inorganic lithium salt. Specifically, the lithium salt may be selected from lithium hexafluorophosphate LiPF. 6 、Lithium bis(trifluoromethanesulfonyl)imide LiN(CF 3 SO 2 ) 2 (abbreviated as LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO 2 F) 2 )(abbreviated as LiFSI), lithium bis(oxalatoborate) LiB(C 2 O 4 ) 2 (abbreviated as LiBOB), lithium difluorooxalate borate LiBF 2 (C 2 O 4 ) (abbreviated as LiDFOB), LiBF 4 、LiClO 4 、LiAsF 6 When used in a sodium ion battery, the electrolyte may be a sodium salt, which may be selected from one or more of an organic sodium salt or an inorganic sodium salt.
[0161] In some embodiments of the present application, the electrolyte includes a lithium salt. Further, the lithium salt includes LiPF 6 and at least one of LiFSI.
[0162] In some embodiments of the present application, the electrolyte includes LiPF 6and LiFSI, LiFSI and LiPF 6 In some embodiments of the present application, the molar concentration of LiFSI in the electrolyte is 0.1-1 mol / L, and the molar ratio of LiPF in the electrolyte is 0.1-5. 6 The molar concentration of LiFSI is 0.2-1.2 mol / L. The higher the content of LiFSI, the more favorable it is for Li + The migration of LiFSI can improve the fast charging performance of the battery. The lower the content of LiFSI, the less corrosion it will cause to the negative electrode current collector, which is beneficial to the safety performance of the battery. 6 The molar ratio is 0.1-5, which can take into account both the fast charging performance and safety of the battery.
[0163] For example, LiFSI and LiPF 6 The molar ratio of can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5, etc., and it can also be any value in the range of 0.1 to 5. The molar concentration of LiFSI in the electrolyte can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1 mol / L, etc., and it can also be any value in the range of 0.1-1 mol / L. LiPF in the electrolyte 6 The molar concentration can be 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, 1.1mol / L or 1.2mol / L, etc., and it can also be any value in the range of 0.2-1.2mol / L.
[0164] In some embodiments of the present application, the LiPF 6 The mass ratio of LiPF to LiFSI is 0.1-10, which is beneficial to balance the fast charging performance and safety of the battery. 6 The mass ratio of LiFSI to LiFSI can be 0.1, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5 or 10, and it can also be any value in the range of 0.1-10.
[0165] In some embodiments of the present application, the electrolyte may optionally include other additives.
[0166] In some embodiments of the present application, the viscosity of the electrolyte is ≤5 mPa·s.
[0167] The viscosity of the electrolyte can be measured using instruments and methods known in the art. For example, non-Newtonian fluids can refer to the rotational viscometer method provided in the national standard GB / T22235-2008 "Determination of Liquid Viscosity". Specifically, a certain mass of electrolyte sample is placed in a sample container and tested using a rotational viscometer with the instrument model DV2TLV produced by Brookfield. At a certain temperature, the shear force exerted on the rotor when it rotates continuously at a constant speed in the sample causes the spring to generate torque, which is proportional to the viscosity, and the viscosity value is obtained. The test equipment meets the following test environmental conditions: 1. External environment of the equipment: temperature is 15-28°C, humidity is RH<80%; 2. Internal environment of the equipment: 2 / 3 of the sample container is immersed in a water bath, the medium is water, and water is used to keep the sample at a constant temperature.
[0168] The reduction of electrolyte viscosity is conducive to the diffusion of lithium ions in the electrolyte, thereby effectively improving the fast charging and power performance of the battery. By controlling the viscosity of the electrolyte to ≤5mPa·s, the battery with the electrolyte has better fast charging and power performance.
[0169] Exemplarily, the viscosity of the electrolyte may be 1 mPa·s, 1.5 mPa·s, 2 mPa·s, 2.5 mPa·s, 3 mPa·s, 3.5 mPa·s, 4 mPa·s, 4.5 mPa·s or 5 mPa·s, etc., and it may also be any value within the range of ≤5 mPa·s.
[0170] After the above introduction to the composition of the electrolyte, its application in the battery cell 20 will be specifically introduced below.
[0171] The method for preparing the battery cell 20 comprises the following steps:
[0172] S101, preparation of positive electrode sheet: positive electrode active material, conductive agent and binder are mixed to obtain a mixture. In the mixture, the mixture is added to the solvent, stirred and mixed evenly to obtain positive electrode active slurry; then the positive electrode active slurry is evenly coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying, cold pressing and cutting. Among them, the positive electrode active material can be a ternary system material, such as: LiNi 0.6 Co 0.2 Mn 0.2 O 2, and a small amount of other positive electrode active materials may be optionally added. The binder may be one or more of styrene-butadiene rubber, water-based acrylic resin, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, polyvinyl alcohol and polyvinyl butyral. The conductive agent may be at least one of conductive carbon black, carbon fiber, carbon nanotube, Ketjen black, graphene or acetylene black. The solvent may be one or more of dimethyl glutarate and N-methylpyrrolidone. A leveling agent, a dispersant, and the like may also be added to the positive electrode active slurry. The positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0173] The coating method may be: scraping, roller coating, slit coating, etc., which is not limited in this application.
[0174] S102, dissolving the negative electrode active material, conductive agent, binder and thickener in a solvent, and mixing them evenly to prepare a negative electrode active slurry; coating the negative electrode active slurry evenly on the negative electrode collector once or multiple times, and obtaining a negative electrode sheet through drying, cold pressing and slitting.
[0175] Among them, the negative electrode active material can adopt the negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material can be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more. The conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The binder may include, but is not limited to, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) One or more. The negative electrode active material layer may also optionally include other additives. As an example, other additives may include, but are not limited to, thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc. The negative electrode current collector may include a metal foil, a three-dimensional porous current collector, or a composite current collector. As a metal foil, copper foil, copper alloy foil, nickel foil, nickel alloy foil, aluminum foil, and aluminum alloy foil may be used. As a three-dimensional porous current collector, a copper mesh, a nickel mesh, a foamed copper, a foamed nickel, and a foamed aluminum may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include, but is not limited to, one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, aluminum, aluminum alloy, silver, and silver alloy. As an example, the polymer material base layer may include, but is not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0176] S103, the prepared positive electrode sheet, negative electrode sheet and separator (for example, polyethylene (PE) porous polymer film) are made into corresponding electrode assemblies according to the Z-shaped stacking structure, and the electrode assembly is vacuum dried at 90°C for 12 hours, and then the positive and negative electrode tabs are ultrasonically welded, the positive electrode uses aluminum tabs, and the negative electrode uses nickel tabs, and the positive and negative electrode tabs are located on the same side of the electrode assembly, and the electrode assembly after the tabs are welded is placed in an aluminum-plastic film of appropriate size for top and side sealing, and the top and side sealing temperature is 145°C, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery is then subjected to the processes of static, hot and cold pressing, formation, aging, shaping, capacity testing, etc. in sequence to obtain a battery cell.
[0177] Among them, the isolation membrane is arranged between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing internal short circuit. The present application has no special restrictions on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. The material of the isolation membrane may include but is not limited to one or more of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP) and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.
[0178] Since additives will participate in the formation of SEI film in the preparation process of battery cells, such as formation and aging, their dosage will be reduced to a certain extent. It has been determined that after the above electrolyte (i.e., in the electrolyte, the mass content b1 of the first additive is 0.2%-2%, the mass content c1 of the second additive in the electrolyte is 0.05%-3.5%, recorded as fresh electrolyte) is applied to the secondary battery and the formation and aging steps are completed, in the electrolyte at this time, the mass content b2 of the first additive in the electrolyte is 0.02%-1%, the mass content c2 of the second additive in the electrolyte is 0%-2%, and to a certain extent, it is positively correlated with the dosage of the first additive and the second additive in the fresh electrolyte. Related; Exemplarily, the mass content b2 of the first additive in the product battery electrolyte can be 0.02%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc., and it can also be any value in the range of 0.02%-1%; Exemplarily, the mass content c2 of the second additive in the product battery electrolyte can be 0%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%, etc., and it can also be any value in the range of 0%-2%, and the mass content of the electrolyte solvent hardly changes.
[0179] In some embodiments of the present application, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the Dv50 of the lithium nickel cobalt manganese oxide is 2μm-15μm.
[0180] In a battery whose positive electrode active material of the positive electrode sheet is lithium nickel cobalt manganese oxide, the first additive can combine with the metal ions on the surface of the positive electrode sheet to form ionic bonds, reduce the phenomenon of lithium over-desorption on the surface of the positive electrode sheet, thereby effectively reducing the occurrence of structural destruction of the positive electrode active material, reducing the side reaction of the electrolyte on the positive electrode sheet side and the gas production problem caused by the side reaction. When the second additive is added to the electrolyte, a SEI film can be further formed on the surface of the negative electrode active material, thereby improving the structural stability of the negative electrode sheet side and improving the life of the battery. Since the ternary system material is more unstable than other positive electrode active materials, it will bring more electrolyte reactions, and the battery life and gas production problems are more obvious. In a battery whose positive electrode active material of the positive electrode sheet is a ternary system material, the electrolyte containing the first additive and the second additive as provided above is used, and the improvement of the battery life is more obvious.
[0181] In this application, Dv50 represents the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%. It can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer with reference to GB / T19077-2016 particle size distribution laser diffraction method, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.
[0182] Exemplarily, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the Dv50 of the lithium nickel cobalt manganese oxide is 2μm-3μm, 2μm-5μm, 2μm-7μm, 2μm-9μm, 2μm-10μm, 2μm-12μm, 2μm-15μm. The positive electrode active material includes lithium nickel cobalt manganese oxide, and the Dv50 of the positive electrode active material is 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm, etc., which can also be any value in the range of 2μm-15μm.
[0183] The smaller the particle size of lithium nickel cobalt manganese oxide, the more reactive sites there are on the surface of lithium nickel cobalt manganese oxide, the faster the lithium ion deintercalation speed is, and the better it can match the lithium ion transmission speed in the electrolyte. In addition, reducing the particle size of lithium nickel cobalt manganese oxide is conducive to reducing the lithium ion transmission impedance and reducing the temperature rise of the battery under the fast charging system. The temperature rise of the battery will cause more side reactions of the solvent in the electrolyte, affecting the battery cycle performance, but if the particle size is too small, it will lead to more side reactions at the interface between lithium nickel cobalt manganese oxide and the electrolyte, worsening gas production and affecting the life of the battery. Controlling the Dv50 of the lithium nickel cobalt manganese oxide positive electrode active material to 2μm-15μm can reduce the side reactions of the electrolyte on the positive electrode side, taking into account the fast charging performance and service life of the battery.
[0184] Furthermore, in some embodiments of the present application, the positive electrode active material includes lithium nickel cobalt manganese oxide, the molar content of nickel element is less than 80% based on the total molar number of transition metals in the lithium nickel cobalt manganese oxide, the Dv50 of the positive electrode active material is 2μm-5μm, and the positive electrode active material includes unagglomerated primary particles.
[0185] In the present application, a primary particle refers to the smallest unit of a particle within a certain identification range. The interior of a primary particle may include defects of any form, but it is impossible to define smaller particles in the primary particle. The primary particle can be in an unagglomerated state or an agglomerated state. The aggregate of the agglomerated primary particles is called a secondary particle. The secondary particles have a clear surface and boundary, but after cutting the cross section of the secondary particles, it can be seen that the secondary particles are formed by the agglomeration of many primary particles. Unagglomerated primary particles refer to the phenomenon that these primary particles do not have obvious inter-particle agglomeration with each other, becoming secondary particles.
[0186] The state of the positive electrode active material in the positive electrode active material layer can be determined by observing the particle morphology of a cross section in the thickness direction of the positive electrode sheet.
[0187] Exemplarily, the molar content of nickel element in lithium nickel cobalt manganese oxide can be selected to be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 79% or any range therebetween.
[0188] For example, the Dv50 of lithium nickel cobalt manganese oxide with a molar content of nickel element less than 80% is 2μm-4μm, 2μm-3μm. As an example, it is 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm or 5μm, which can also be any value in the range of 2μm-5μm.
[0189] The molar content of nickel element is less than 80%, which is beneficial to reduce the probability of nickel dissolution of positive electrode active materials under high voltage (charging cut-off voltage ≥ 4.3V) and improve the withstand voltage of positive electrode active materials. The combination of low nickel components and unagglomerated primary particles can further reduce the degree of side reactions between positive electrode active materials and carboxylic acid ester solvents, reduce the probability of cracking of positive electrode active materials during high voltage charging and discharging, and improve the cycle performance of battery cells.
[0190] In some embodiments of the present application, the positive electrode active material includes lithium nickel cobalt manganese oxide, based on the total molar number of transition metals in the positive electrode active material, the molar content of nickel element is greater than or equal to 80%, the Dv50 of the positive electrode active material is 6μm-15μm, and the positive electrode active material includes secondary particles formed by agglomeration of primary particles.
[0191] Exemplarily, the molar content of nickel in lithium nickel cobalt manganese oxide is 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or any range therebetween.
[0192] In some embodiments of the present application, lithium nickel cobalt manganese oxide includes LiNi 0.83 Co 0.07 Mn 0.1 O 2 、LiNi 0.6 Co 0.2 Mn 0.2 O 2 .
[0193] For example, the Dv50 of lithium nickel cobalt manganese oxide having a molar content of nickel element greater than or equal to 80% is 6μm-14μm, 6μm-13μm, 6μm-12μm, 6μm-11μm, 6μm-10μm, 6μm-9μm, 6μm-8μm, 6μm-7μm. As an example, Dv50 is 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm or 14μm, which can also be any value in the range of 6μm-15μm.
[0194] In some embodiments of the present application, the positive electrode active material lithium nickel cobalt manganese oxide includes secondary particles, and the average particle size of the primary particles in the secondary particles can be 0.1μm-1.5μm, as an example, 0.1μm, 0.3μm, 0.5μm, 0.7μm, 0.9μm, 0.11μm, 0.13μm, 0.15μm, it can also be any value in the range of 0.1μm-1.5μm.
[0195] The average particle size of the primary particles in the secondary particles can be tested by any known method in the art. As an example, a cross section in the thickness direction of the positive electrode sheet is obtained, and particles of any 10 areas of the same size and shape in the same scanning electron microscope image (SEM) under 10kv and 30k magnification are observed. The 10 areas are then subdivided into 5 positions in the four corners and the center, and the mean particle size of any primary particle at each position under the magnification is selected, and the mean particle size results of the 5 positions in the four corners and the center are averaged to obtain the mean particle size of the primary particles in the area, and then the particle size of the primary particles obtained in the 10 areas is averaged as the average particle size of the primary particles. Specifically, the average value of the major diameter and minor diameter of each particle is taken as the mean particle size of the particle.
[0196] Forming high-nickel materials into large-sized secondary particles is beneficial to simultaneously increase the specific capacity of the positive electrode active material and the gradation of the positive electrode sheet, and improve the energy density of the battery. At the same time, the secondary particles are composed of small-sized primary particles, which can shorten the transmission distance of lithium ions, increase the number of embedded end faces, reduce the DC impedance of the battery cell, and improve the power performance of the battery cell.
[0197] In some embodiments of the present application, the positive electrode active material includes LiNi 0.6 Co 0.2 Mn 0.2 O 2 , the Dv50 of the positive electrode active material is 2μm-4μm. In some embodiments of the present application, the positive electrode active material includes LiNi 0.83 Co 0.07 Mn 0.1 O 2 , the Dv50 of the positive electrode active material is 7μm-10μm.
[0198] In some embodiments of the present application, lithium nickel cobalt manganese oxide may be doped with at least one metal element selected from the group consisting of Fe, Mg, Fe, Al, Cu, and Ti.
[0199] Doping metal elements in lithium nickel cobalt manganese oxide can form more conduction paths inside the positive electrode active material, thereby increasing the deintercalation speed of lithium ions, which can match the transmission speed of lithium ions in the electrolyte, and help reduce the lithium ion transmission impedance and the temperature rise of the battery under the fast charging system. At the same time, during the charging and discharging process, especially when the battery is at a high voltage, the transition metals (such as nickel, cobalt, manganese, etc.) in the positive electrode active material may dissolve into the electrolyte, and lithium nickel cobalt manganese oxide doped with metal elements can improve the structural stability of the positive electrode active material and ensure the smooth deintercalation of lithium ions.
[0200] In some embodiments of the present application, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, the positive electrode active material includes a lithium-containing phosphate, and the Dv50 of the positive electrode active material is 0.3μm-2μm. In a battery in which the positive electrode active material of the positive electrode sheet is a lithium-containing phosphate material, the additive can form a stable SEI film on the negative electrode sheet, block the contact between the solvent and the negative electrode sheet, reduce the occurrence of solvent reduction, inhibit further side reactions on the negative electrode sheet side, and improve the life of the battery.
[0201] In some embodiments of the present application, the general composition formula of the lithium-containing phosphate is as follows:
[0202] Li x1 A y1 Me a1 M b1 P 1-c1 X c1 Yz1 ,
[0203] Among them, 0.5≤x1≤1.3, 0≤y1≤1.3, and 0.7≤x1+y1≤1.3; 0.9≤a1≤1.5, 0≤b1≤0.5, and 0.9≤a1+b1≤1.5; 0≤c1≤0.5; 3≤z1≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; Y includes one or more of O and F.
[0204] The lithium-containing phosphate having the above components has good structural stability and low irreversible loss during fast charging, thereby improving the cycle stability of the battery cell.
[0205] In some embodiments of the present application, the lithium-containing phosphate has an olivine structure, including but not limited to lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate and one or more of their respective doped modified materials, coated modified materials, and composite modified materials.
[0206] In some embodiments of the present application, the Dv50 of the positive electrode active material containing lithium phosphate can be 0.3μm, 0.5μm, 0.7μm, 0.9μm, 1.1μm, 1.3μm, 1.5μm, 1.7μm, 1.9μm or 2.0μm, and it can also be any value in the range of 0.3μm-2.0μm.
[0207] The smaller the particle size of the lithium-phosphate material, the more reaction sites the lithium-phosphate material has, the faster the lithium-ion deintercalation speed is, and the better it can match the lithium-ion transmission speed in the electrolyte. In addition, reducing the particle size of the lithium-iron material is conducive to reducing the lithium-ion transmission impedance and reducing the temperature rise of the battery under the fast charging system. The battery temperature rise will cause more side reactions in the electrolyte and affect the battery cycle life. However, if the particle size is too small, the lithium-phosphate material will adsorb more water, which will not only hydrolyze the solvent in the electrolyte, causing the battery internal resistance to increase and affecting the battery cycle life, but also make the SEI film unstable, resulting in continuous electrolyte decomposition and irreversible consumption of lithium ions, thereby affecting the battery cycle performance. Controlling the Dv50 of the lithium-phosphate material to 0.3μm-2μm can reduce the hydrolysis of the electrolyte, while improving the battery fast charging performance and taking into account the battery cycle performance and service life.
[0208] In some embodiments, the positive electrode active material containing lithium phosphate includes unagglomerated primary particles and / or secondary particles formed by agglomeration of primary particles, and the average particle size of the primary particles of the positive electrode active material containing lithium phosphate is 50 nm-300 nm.
[0209] In some embodiments, the average particle size of the primary particles of the positive electrode active material containing lithium phosphate can be selected to be 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm or any numerical range therebetween.
[0210] The lithium-containing phosphate with an average particle size of primary particles within the above range has both a shorter ion transmission path and a low lithium ion transmission impedance, which can match the liquid phase transmission rate of lithium ions in the electrolyte and take into account the cycle life of the battery cell. The positive electrode active material with small primary particles is not conducive to the improvement of the active material layer density. After it is aggregated into secondary particles, the Dv50 is within the range of 0.3μm-2μm, which is conducive to further improving the cycle performance and service life of the battery.
[0211] In this application, for the positive electrode active material (such as lithium-containing phosphate or lithium nickel cobalt manganese oxide), the statistics of the primary particle size can be carried out in the following way. As an example, the battery is disassembled to obtain the positive electrode sheet, the active material layer of the positive electrode sheet is peeled off, acetone is fully washed, filtered and dried to obtain a powder. Take 0.05g of the evenly mixed powder and dissolve it in 40mL of anhydrous ethanol, then add an appropriate amount of dispersant, stir evenly to obtain a suspension, take 2mL of the suspension and 2mL of anhydrous ethanol and mix them for ultrasonic treatment, the ultrasonic power is 480W, the ultrasonic time is 5min, and a uniformly dispersed suspension is obtained. Take an appropriate amount of the middle layer suspension for transmission electron microscopy test to obtain a transmission electron microscope image. Select 5-10 transmission electron microscope images with a number of 50 to 100 particles as the sampling area, ensure that at least 500 particles are tested, and then the projected area of each primary particle in each sampling area can be counted by the Avizo 3D software image processing software, that is, the primary particle cross-sectional area S. When identifying primary particles, for particles with obvious adhesion, manual identification and software identification can be combined to determine whether the particle is a single primary particle or two secondary particles. The equivalent circle method is used to obtain the equivalent circle diameter of the primary particle, which is the primary particle size.
[0212] In some embodiments of the present application, the negative electrode sheet includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material and lithium metal.
[0213] In some embodiments of the present application, graphite includes artificial graphite. Artificial graphite has fewer defects, can reduce the side reaction between the electrolyte and artificial graphite, reduce the gas production of the negative electrode, and improve the gas production defects of the battery. In addition, artificial graphite has a small specific surface area. When the electrolyte forms an SEI film on the surface of artificial graphite, the amount of the first additive and the second additive can be reduced compared to the use of natural graphite negative electrode active materials.
[0214] In some embodiments of the present application, the negative electrode active material includes secondary particles, and the Dv50 of the secondary particles is 5μm-18μm. The particle state of the negative electrode active material in the negative electrode active material layer can be determined by observing the particle morphology of the cross section in the thickness direction of the negative electrode sheet. The Dv50 of the negative electrode active material graphite can be obtained by measuring with a laser particle size analyzer.
[0215] Secondary particles are composed of many small grains, each with a grain boundary between them, which can provide additional paths for lithium ions, increase the reactive sites of negative electrode active materials, and provide suitable embedding end faces for lithium ions, thereby increasing the de-embedding speed of lithium ions and improving fast charging performance. When the Dv50 of the negative electrode active material is too small, the side reactions between the negative electrode active material and the electrolyte increase, affecting the battery cycle life. When the Dv50 of the negative electrode active material is too large, the process is difficult to implement and the compaction density of the electrode sheet is affected. Controlling the negative electrode active material to be a secondary particle and the Dv50 of the negative electrode active material to be 5μm-18μm can make the end face of the negative electrode active material suitable for lithium ion embedding, which can match the lithium ion transfer rate of the electrolyte and improve the fast charging performance of the battery. At the same time, the negative electrode active material synergizes with the first and second additives to form a dense SEI film on the surface of the negative electrode active material, thereby increasing the life of the battery.
[0216] Exemplarily, the secondary particle Dv50 is 5 μm-10 μm, 5 μm-12 μm, 5 μm-15 μm, 5 μm-17 μm. The secondary particle Dv50 is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm or 18 μm, etc., and it can also be any value in the range of 5 μm-18 μm.
[0217] In some embodiments of the present application, the air oxidation temperature T 0 It is 630℃-730℃.
[0218] In this document, the term "air oxidation temperature" refers to the air oxidation temperature T0 are the temperature corresponding to 500℃ and T on the thermogravimetric curve of the negative electrode active material. 1 The temperature corresponding to the intersection of the two tangent lines at the two temperature points, T 1 The temperature is the peak top temperature of the maximum area peak in the differential thermogravimetric curve of the negative electrode active material. The thermogravimetric curve and the differential thermogravimetric curve can be obtained by thermogravimetric analysis under the following conditions: weigh the sample mass 10±0.05 mg, set the relevant parameters of the thermogravimetric analyzer: the purge gas is air and the air flow rate is 60 mL / min, the heating rate is 5°C / min, and the test temperature range is 35°C-950°C.
[0219] The air oxidation temperature of the negative electrode active material can accurately indicate the temperature at which the negative electrode active material begins to lose weight due to air oxidation, and thus can accurately reflect the end faces and defect counts of the negative electrode active material. 0 When the temperature is 630℃-730℃, the negative electrode active material contains a moderate number of end faces and defects, has good lithium ion and electron transmission performance, can match the lithium ion transmission rate of the electrolyte, and improve the fast charging performance of the battery. At the same time, the negative electrode active material can have more lithium insertion sites, which is beneficial to improve the energy density of the battery. It can also make the first additive and the second additive adhere to the surface of the negative electrode active material earlier and more efficiently to form a dense SEI film, reduce the side reactions of the solvent and the negative electrode, and improve the fast charging performance of the battery while taking into account the cycle performance and service life of the battery.
[0220] For example, the air oxidation temperature of the negative electrode active material is T 0 640℃-730℃, 660℃-730℃, 680℃-730℃, 700℃-730℃, 710℃-730℃. Air oxidation temperature T of negative electrode active material 0 It is 630℃, 640℃, 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, 710℃, 720℃ or 730℃, etc. It can also be any value in the range of 630℃-730℃.
[0221] In some embodiments of the present application, the negative electrode active material includes a silicon-based material, and the mass proportion of the silicon-based material in the negative electrode active material layer does not exceed 25%. Silicon-based materials are beneficial to the energy density and other performance of the battery. However, in the present application, some carboxylic acid ester solvents (for example: ethyl acetate, methyl acetate, methyl formate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, propyl butyrate, butyl butyrate, isopropyl acetate and isoamyl acetate) are prone to produce proton hydrogen, and silicon-based materials are more sensitive to proton hydrogen. Controlling its mass proportion to no more than 25% is beneficial to the cycle life of the battery.
[0222] In some embodiments of the present application, the charging time t of the battery from 0% SOC to 80% SOC satisfies: t≤18.5min. The battery has a short charging time and a strong fast charging capability.
[0223] Exemplarily, the charging time for the battery to charge from 0% SOC to 80% SOC is t≤17.1 min, t≤16.5 min, t≤15.1 min, t≤14.1 min, t≤13.3 min, t≤12.6 min, or t≤11.1 min.
[0224] In some embodiments of the present application, the charging time t for charging the battery from 0% SOC to 80% SOC is 11 min-18.5 min.
[0225] Exemplarily, the charging time t for the battery to charge from 0% SOC to 80% SOC is 18.5 min, 18.1 min, 17.1 min, 16.5 min, 15.2 min, 14.8 min, 14.4 min, 14.0 min, 13.6 min, 13.2 min, 12.8 min, 12.4 min, 12.0 min, 11.6 min, 11.4 min or 11.1 min, etc., and it can also be any value in the range of 11 min-18.5 min.
[0226] Next, one or more embodiments are described in more detail with reference to the following examples. Of course, these examples do not limit the scope of one or more embodiments.
[0227] Examples 1-24, Examples 28-32 and Comparative Examples 1-2
[0228]
Preparation of positive electrode
[0229] The positive electrode active material ternary material, the binder polyvinylidene fluoride, and the conductive agent acetylene black are mixed in a weight ratio of 98:1:1 and dissolved in a solvent N-methylpyrrolidone (NMP) to form a positive electrode slurry, and then the slurry is coated on the current collector aluminum foil, and after drying, it is cold pressed, trimmed, cut into pieces, and striped to make the positive electrode sheet of the lithium-ion battery.
[0230]
Preparation of negative electrode sheet
[0231] The negative electrode active material artificial graphite, the conductive agent carbon black, the thickener CMC-Na, and the adhesive styrene-butadiene rubber (SBR) are mixed in a weight ratio of 96:2:1:1 and dissolved in a solvent deionized water to form a negative electrode slurry; the slurry is then coated on a current collector copper foil, and after drying, it is cold pressed, trimmed, cut into pieces, and stripped to form a negative electrode sheet for a lithium-ion battery.
[0232]
Preparation of electrolyte
[0233] The preparation of the electrolyte is carried out in an argon atmosphere glove box with a water content of <10ppm. First, the carbonate compound solvent and / or the carboxylate compound solvent are mixed in a certain proportion, then the lithium salt is added, and finally the additives are added in sequence to complete the preparation of our electrolyte. Among them, the content of each organic solvent is the weight percentage calculated based on the total weight of the organic solvent, and the content of each lithium salt is the weight percentage calculated based on the total weight of the electrolyte.
[0234]
Isolation film
[0235] Polypropylene film is used as the isolation film.
[0236] Preparation of battery cells
[0237] The prepared positive electrode sheet, negative electrode sheet and separator are made into corresponding electrode assemblies according to the Z-shaped stacking structure, and the electrode assembly is vacuum dried at 90°C for 12 hours, followed by ultrasonic welding of positive and negative electrode tabs. The positive electrode uses aluminum tabs and the negative electrode uses nickel tabs. The positive and negative electrode tabs are located on the same side of the electrode assembly. The electrode assembly after the tabs are welded is placed in an aluminum-plastic film of appropriate size for top and side sealing. The top and side sealing temperature is 145°C, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes the processes of static, hot and cold pressing, formation, shaping, capacity testing, etc. to obtain a battery cell.
[0238] The preparation methods of Examples 25-27 are basically the same as those of Example 1, except that the steps for preparing the positive electrode sheet are changed to: preparing the positive electrode active material containing lithium phosphate material LiFePO 4 The positive electrode slurry is prepared by mixing the binder polyvinylidene fluoride and the conductive agent acetylene black in a weight ratio of 96:2:2 and dissolving them in a solvent N-methylpyrrolidone (NMP). The slurry is then coated on a current collector aluminum foil and, after drying, cold pressed, trimmed, cut into pieces, and stripped to prepare a positive electrode sheet for a lithium-ion battery.
[0239] The main parameter controls of Examples 1 to 32 and Comparative Examples 1 to 2 are shown in Tables 1 and 2 below.
[0240] Table 1
[0241]
[0242]
[0243] In the table, “ / ” means that the substance does not exist.
[0244] Table 2
[0245]
[0246]
[0247] Dv50 test of positive electrode active materials and negative electrode active materials: The average particle size, i.e., Dv50, of the positive electrode active materials and negative electrode active materials was measured using a Mastersizer 2000E laser particle size analyzer produced by Malvern Instruments Ltd., UK.
[0248] Air oxidation temperature T 0 Test: The test was conducted using a German NETZSCH STA449F3 synchronous thermal analyzer. First, 10 ± 0.05 mg of artificial graphite sample was weighed and placed on a flat Al 2 O 3 In the crucible, do not cover the lid; set the instrument parameters: the purge gas is air and the airflow rate is set to 60mL / min, the protective gas is nitrogen and the airflow rate is set to 20mL / min; set the heating rate to 5℃ / min, and the test temperature range is 35℃~950℃. Among them, when the temperature is lower than 500℃, since there is no characteristic peak at this stage, rapid heating can be performed, for example, the heating rate is set to 10℃ / min. After the thermogravimetric test, the thermogravimetric curve (TG) and differential thermogravimetric curve (DTG) of the composite graphite material are obtained, and the peak top temperature T of the maximum area peak is read from the differential thermogravimetric curve. 1 , and the corresponding temperatures at 500℃ and T 1 The intersection of the two tangent lines at the two temperature points corresponds to the temperature on the thermogravimetric curve, which is the air oxidation temperature T of the artificial graphite sample. 0 .
[0249] The performance test was performed on the batteries provided in each embodiment and comparative example, and the performance test specifically included:
[0250] Electrolyte viscosity test: Take a certain mass of electrolyte sample and place it in a sample container, and use a rotational viscometer model DV2TLV produced by Brookfield for testing. At a certain temperature, the shear force applied to the rotor when it rotates continuously at a constant speed in the sample causes the spring to generate torque, which is proportional to the viscosity, and the viscosity value is obtained. The test equipment meets the following test environment conditions: 1. Equipment external environment: temperature is 15-28℃, humidity is RH<80%; 2. Equipment internal environment: 2 / 3 of the sample container is immersed in a water bath, the medium is water, and water is used to keep the sample at a constant temperature.
[0251] Fast charging capability test: The batteries of the above-mentioned embodiments and comparative examples are charged and discharged for the first time at a current of 1C (i.e., the current value at which the theoretical capacity is completely discharged within 1 hour), specifically including: at 35°C, the battery is charged at a constant current of 1C to a voltage of 4.4V, then charged at a constant voltage to a current ≤0.05C, left to stand for 5 minutes, and then discharged at a constant current of 0.33C to a voltage of 2.8V, and its actual capacity is recorded as C0. Then each battery is charged with a constant current of 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0, 3.5C0, 4C0, 4.5C0, and 5C0 in sequence to a full battery charge cutoff voltage of 4.4V or a negative electrode cutoff potential of 0V (whichever is reached first). After each charge is completed, it is necessary to discharge with 1C0 to a full battery discharge cutoff voltage of 2.8V. Record the SOC (State of Charge) at different charge rates to 10%, 20%, 30%, ..., 80%. Charge, state of charge, when "SOC = 0" means the battery is fully discharged, when "SOC = 100%" means the battery is fully charged) the corresponding negative electrode potential, draw the charge rate-negative electrode potential curve under different SOC states, and obtain the charge rate corresponding to the negative electrode potential of 0V under different SOC states after linear fitting. The charge rate is the charging window under the SOC state, which is recorded as C (10% SOC), C (20% SOC), C (30% SOC), C (40% SOC), C (5 0%SOC)、C(60%SOC)、C(70%SOC)、C(80%SOC), according to the formula (60 / C(10%SOC)+60 / C(20%SOC)+60 / C(30%SOC)+60 / C(40%SOC)+60 / C(50%SOC)+60 / C(60%SOC)+60 / C(70%SOC)+60 / (C80%SOC))×10%, the charging time T of the battery from 0 to 80%SOC is calculated in min. The shorter the time, the better the fast charging performance of the battery.
[0252] The cycle performance test process is as follows: at 45°C, the prepared battery is charged to 4.25V at a constant current of 1C, then charged at a constant voltage of 4.25V until the current drops to 0.05C, and after standing for 5 minutes, discharged to 2.5V at a constant current of 1C. This is the first charge / discharge cycle of the battery, and the discharge capacity of this time is recorded as the discharge capacity of the first cycle of the battery (C1); repeat the above steps for the same battery, and the process capacity of the battery after the nth cycle (Cn), the capacity retention rate after n cycles = Cn / C1×100%. Record the number of cycles at which the cycle capacity retention rate is 80%.
[0253] The test results are shown in the following table:
[0254]
[0255] By comparing the data of the embodiments and the comparative examples, it can be obtained that the embodiments of the present application use first additives such as fluorophosphates and borates and second additives such as vinyl sulfate compounds in the electrolyte, so that the battery has better fast charging performance and longer life, wherein the charging time required for 0-80% SOC is within 18.5min, and the number of cycles with a cycle capacity retention rate of 80% is more than 1200 cycles.
[0256] By comparing the data of Examples 1 to 3, it can be obtained that with the increase of the content of carboxylic acid ester solvents in the electrolyte, the fast charging performance of the battery shows a trend of getting better and better, while the life of the battery shows a trend of gradually getting worse. According to this trend change, it is inferred that when the mass content a1 of the carboxylic acid ester solvent is in the range of 25%-70%, the fast charging performance and life of the battery can meet the requirements.
[0257] By comparing the data of Example 1 and Examples 4 to 9, it can be obtained that with the increase of the content of the first additive in the electrolyte, the fast charging performance of the battery shows a trend of gradually getting worse, while the life of the battery shows a trend of getting better and better. When the content of the first additive is 0.15%-2.5%, the performance of the battery satisfies: the charging time required for 0-80% SOC is within 13.1min, and the number of cycles with a cycle capacity retention rate of 80% is more than 1200 cycles; further, when the content of the first additive is 0.5%-1.5%, the performance of the battery satisfies: the charging time required for 0-80% SOC is within 12.7min, and the number of cycles with a cycle capacity retention rate of 80% is more than 1430 cycles.
[0258] By comparing the data of Example 2 and Examples 10 to 13, it can be obtained that with the increase of the content of the second additive in the electrolyte, the fast charging performance of the battery shows a trend of gradually getting worse, while the life of the battery shows a trend of getting better and better. When the content of the second additive is 0.05%-3.5%, the performance of the battery satisfies: the charging time required for 0-80% SOC is within 14.2min, and the number of cycles with a cycle capacity retention rate of 80% is more than 1580 cycles; further, when the content of the second additive is 0.1%-2.5%, the performance of the battery satisfies: the charging time required for 0-80% SOC is within 14min, and the number of cycles with a cycle capacity retention rate of 80% is more than 1640 cycles.
[0259] By comparing the data of Examples 14 to 16, it can be seen that different compound combinations of the first additive and the second additive can achieve better fast charging performance and longer life.
[0260] According to the data of Example 1, Example 17 to Example 18, based on the total molar number of transition metals in lithium nickel cobalt manganese oxide, the molar content of nickel element accounts for less than 80%, and the Dv50 of the positive electrode active material is in the range of 2μm-4μm. As Dv50 increases, the fast charging performance of the battery shows a trend of gradually getting worse, while the life of the battery shows a trend of getting better and better. The performance of the battery meets the following requirements: the charging time required for 0-80% SOC is within 12.6min, and the number of cycles with a cycle capacity retention rate of 80% is more than 1340 cycles. According to the trend, based on the total molar number of transition metals in the positive electrode active material, the positive electrode active material with a molar content of nickel element accounting for less than 80% Dv50 within 2μm-5μm can achieve better fast charging performance and longer life.
[0261] According to the data of Examples 19 to 20, based on the total molar number of transition metals in lithium nickel cobalt manganese oxide, the molar content of nickel element accounts for greater than or equal to 80%, and when the Dv50 of the positive electrode active material is 7μm-10μm, as the Dv50 of lithium nickel cobalt manganese oxide increases, the fast charging performance of the battery shows a trend of gradually getting worse, while the life of the battery shows a trend of getting better and better, and the performance of the battery meets: the charging time required for 0-80% SOC is within 12.8min, and the number of cycles with a cycle capacity retention rate of 80% is more than 1680 cycles. According to the trend, it is speculated that based on the total molar number of transition metals in the positive electrode active material, the Dv50 of the positive electrode active material with a molar content of nickel element greater than or equal to 80% is within 6μm-18μm, which can achieve better fast charging performance and longer life.
[0262] By comparing the data of Example 1 with those of Example 21 to Example 22, it can be seen that as the Dv50 of the secondary particles of the negative electrode active material increases, the fast charging performance of the battery shows a trend of gradually getting worse, while the battery life shows a trend of getting better and better. When the Dv50 of the secondary particles of the negative electrode active material is 6μm-15μm, the performance of the battery meets the following requirements: the charging time required for 0-80% SOC is within 13.1min, and the number of cycles with a cycle capacity retention rate of 80% is more than 1360 cycles. According to the trend, it is speculated that when the Dv50 of the secondary particles of the negative electrode active material is within 5μm-18μm, better fast charging performance and longer life can be achieved.
[0263] By comparing the data of Example 1 with Examples 23 to 24, it can be obtained that as the air oxidation temperature of the negative electrode active material increases, the fast charging performance of the battery shows a trend of gradually deteriorating, while the battery life shows a trend of getting better and better. When the air oxidation temperature of the negative electrode active material is 630°C-730°C, the performance of the battery meets the following requirements: the charging time required for 0-80% SOC is within 13.2min, and the number of cycles with a cycle capacity retention rate of 80% is more than 1460 cycles.
[0264] By comparing the data of Examples 25 to 27, it can be seen that using different compound combinations of the first additive and the second additive can achieve better fast charging performance and longer life in the lithium phosphate positive electrode active material system.
[0265] By comparing the data of Examples 28 to 32, it can be seen that better fast charging performance and longer life can be achieved by using different compound combinations of the first additive and the second additive in different carbonate solvent systems.
[0266] The batteries provided in the embodiments and comparative examples are applied to automobiles, and the contents of the first additive and the second additive in the electrolyte are detected after the automobiles have been driven for 10,000 kilometers, or the batteries provided in the embodiments and comparative examples are cycled for 25 times and the contents of the first additive and the second additive in the electrolyte are detected. The test method is as follows:
[0267] In a glove box filled with nitrogen, 500 μl of deuterated reagent was added to the NMR tube, 100 μl of non-aqueous electrolyte sample was added to the NMR tube, and the NMR tube was shaken to dissolve the non-aqueous electrolyte into the deuterated reagent. The test was performed using the Oxford Instruments X-Pulse desktop NMR spectrometer. Since non-aqueous electrolytes are very sensitive to moisture, the NMR test and sample preparation were performed in a nitrogen atmosphere (H 2 O content is less than 0.1ppm, O 2 The content is less than 0.1ppm), and the test-related instruments also need to be pre-washed with pure water and dried in a vacuum environment at 60°C for more than 48 hours. Among them, the deuterated reagent is prepared according to the following steps: deuterated dimethyl sulfoxide (DMSO-d6), deuterated acetonitrile and trifluoromethylbenzene are dried with 4A molecular sieves at a temperature above 25°C for more than 3 days to ensure that the water content of all reagents is less than 3ppm. The moisture test instrument can use the 831KF coulometric moisture tester of Swiss Metrom Co., Ltd. After that, 10ml of dried DMSO-d6 and 300μl of dried internal standard trifluoromethylbenzene are mixed evenly in a glove box filled with nitrogen to obtain a first solution, 10ml of dried deuterated acetonitrile and 300μl of dried internal standard trifluoromethylbenzene are mixed evenly to obtain a second solution, and the first solution and the second solution are mixed evenly to obtain a deuterated reagent.
[0268] The results are shown in the following table (since the contents of the first additive and the second additive after operation are positively correlated with the contents of the first additive and the second additive in the fresh electrolyte, only part of the example data is shown to illustrate the trend):
[0269]
[0270]
[0271] In the table, “ / ” means the value was not detected.
[0272] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An electrolyte, characterized in that: The electrolyte comprises a first additive and a second additive, wherein the first additive comprises at least one of fluorophosphate and borate, and the second additive comprises a vinyl sulfate compound.
2. The electrolyte according to claim 1, characterized in that The mass content b1 of the first additive in the electrolyte is 0.15%-2.5%; and / or The mass content c1 of the second additive in the electrolyte is 0.05%-3.5%.
3. The electrolyte according to any one of claims 1 to 2, characterized in that The mass content b1 of the first additive in the electrolyte is 0.5%-1.5%; and / or The mass content c1 of the second additive in the electrolyte is 0.1%-2.5%.
4. The electrolyte according to any one of claims 1 to 3, characterized in that The fluorophosphate comprises at least one of monofluorophosphate and difluorophosphate; and / or The borate comprises at least one of tetrafluoroborate, bisoxalatoborate and fluorine-containing oxalatoborate; and / or The fluorophosphate and borate independently include at least one of a lithium salt, a sodium salt and a potassium salt; and / or The vinyl sulfate compounds include At least one of .
5. The electrolyte according to any one of claims 1 to 4, characterized in that The first additive comprises at least one of lithium difluorophosphate and lithium bis(oxalatoborate); and / or The second additive includes At least one of .
6. The electrolyte according to claim 5, characterized in that The mass ratio of the lithium difluorophosphate to the lithium difluorooxalatoborate is 1:(0.05-15).
7. The electrolyte according to any one of claims 1 to 6, characterized in that The second additive includes a sulfonate compound, the mass content of the sulfonate compound in the electrolyte is 0.05%-0.5%, and / or the sulfonate compound includes At least one of .
8. The electrolyte according to claim 7, characterized in that The electrolyte includes Said With the The mass ratio is 1:(0.25-7); or The electrolyte includes Said The mass ratio is 1:(0.25-7).
9. The electrolyte according to any one of claims 1 to 8, characterized in that The electrolyte includes a solvent, and the solvent includes at least one of a carboxylate compound and a carbonate compound. The carboxylic acid ester compound includes R1-COO-R2, wherein R1 includes H or a C1-C5 alkyl group, and R2 includes a C1-C5 alkyl group. The carbonate compounds include At least one of the following, wherein R3 comprises a C2-C3 alkylene group, R4 comprises a C1-C2 alkyl group, and R5 comprises a C1-C2 alkyl group.
10. The electrolyte according to claim 9, characterized in that The carboxylate compound comprises at least one of ethyl acetate, methyl acetate, methyl formate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, propyl butyrate, butyl butyrate, isopropyl acetate and isoamyl acetate; and / or The carbonate compound includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate and dimethyl carbonate.
11. The electrolyte according to claim 9 or 10, characterized in that The mass content of the carboxylic acid ester compound in the electrolyte is 10%-70%; or The mass content of the carbonate compound in the electrolyte is 30%-100%.
12. The electrolyte according to any one of claims 1 to 11, characterized in that The electrolyte includes an electrolyte, the electrolyte includes a lithium salt, and the lithium salt includes at least one of LiPF6 and LiFSI.
13. The electrolyte according to claim 12, characterized in that The electrolyte comprises LiPF6 and LiFSI, the molar ratio of LiFSI to LiPF6 is 0.1-5; and / or the mass ratio of LiPF6 to LiFSI is 0.1-10.
14. The electrolyte according to any one of claims 1 to 13, characterized in that The viscosity of the electrolyte is ≤5 mPa·s.
15. A battery cell, characterized in that: The battery cell uses the electrolyte according to any one of claims 1 to 14.
16. The battery cell according to claim 15, characterized in that: The mass content b2 of the first additive in the electrolyte is 0%-1%; and / or The mass content c2 of the second additive in the electrolyte is 0%-2%.
17. The battery cell according to claim 15 or 16, characterized in that: The battery cell further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material layer, and the positive electrode active material layer comprises a positive electrode active material. The positive electrode active material comprises lithium nickel cobalt manganese oxide, and the Dv50 of the lithium nickel cobalt manganese oxide is 2 μm-15 μm; or The positive electrode active material includes a lithium-containing phosphate, and the Dv50 of the lithium-containing phosphate is 0.3 μm-2 μm.
18. The battery cell according to claim 17, characterized in that: The positive electrode active material comprises lithium nickel cobalt manganese oxide, the molar content of nickel element accounts for less than 80% based on the total molar number of transition metals in the positive electrode active material, the Dv50 of the positive electrode active material is 2 μm-5 μm, and the positive electrode active material comprises unagglomerated primary particles; or The positive electrode active material comprises lithium nickel cobalt manganese oxide, the molar content of nickel element is greater than or equal to 80% based on the total molar number of transition metals in the positive electrode active material, the Dv50 of the positive electrode active material is 6 μm-15 μm, the positive electrode active material comprises secondary particles formed by agglomeration of primary particles, and the average particle size of the primary particles in the secondary particles is 0.1 μm-1.5 μm; or, The positive electrode active material comprises unagglomerated primary particles and / or lithium-containing phosphate formed by agglomerating primary particles into secondary particles. The average particle size of the primary particles of the positive electrode active material is 50 nm to 300 nm.
19. The battery cell according to any one of claims 15 to 18, characterized in that: The battery cell further includes a negative electrode sheet including a negative electrode active material layer, the negative electrode active material layer including a negative electrode active material, and the negative electrode active material includes at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based material and lithium metal.
20. The battery cell according to any one of claims 15 to 19, characterized in that: The negative electrode active material comprises artificial graphite; and / or The negative electrode active material comprises secondary particles, wherein the Dv50 of the secondary particles is 5 μm-18 μm; and / or The air oxidation temperature T0 of the negative electrode active material is 630°C-730°C.
21. The battery cell according to claim 19, characterized in that: The negative electrode active material includes a silicon-based material, and the mass proportion of the silicon-based material in the negative electrode active material layer does not exceed 25%.
22. A battery, characterized in that: The battery comprises the battery cell according to any one of claims 15 to 21.
23. The battery according to claim 22, characterized in that The charging time t of the battery from 0% SOC to 80% SOC satisfies: t≤18.5 min.
24. An electrical device, characterized in that: The electrical device comprises the battery cell according to any one of claims 15 to 21 or the battery according to claim 22 or 23.
Citation Information
Cited By
Lithium ion secondary battery, preparation method thereof and electric device
CN120073044A
Lithium-ion secondary battery, method for manufacturing the same, and electric device
CN120073044B
Method and system for supplementing electrolyte in battery cell
CN121035554A
Lithium battery, energy storage device and power utilization system
CN122117880A
Lithium battery, energy storage device and power utilization system
CN122117880B